Rozwój gospodarki Unii Europejskiej – Strategia Lizbońska, a nowy plan „Europa 2020” - STANKIEWICZ, WOJCIECH (Rocznik Integracji Europejskiej, 2012)
The article points out that the co-ordination of economic policy plays a significant role in the proper functioning of an economy. In 2000, an economic development plan, known as the Lisbon Strategy, was designed within the framework of the European Union. The plan was ambitious and contained a number of assumptions that were to guarantee the unrivalled international competitiveness of Europe upon their implementation. On account of poor performance results the strategy was reviewed in 2005, yet it still failed to achieve the desired objectives. The reason for that were exaggerated ambitions that were not adjusted to the changing economic conditions in the world. In 2010, the Lisbon Strategy was replaced by the „Europe 2020” strategy, which may be less ambitious, but its assumptions are more realistic. The objective of the „Europe 2020” strategy is primarily to recover quickly from the crisis and prevent similar ones in the future, as well as to achieve sustainable economic growth while taking a more environmentally sound course.